Shed lay-out affects physiological responses and semen quality of crossbred bulls during summer season - SIROHI, A S; CHAND, N; TYAGI, S; KUMAR, S; SHARMA, A; HEMLATA; SINGH, C P (The Indian Journal of Animal Sciences, 2017)
The present study was conducted to assess the effect of sheds with two different designs on physiological responses and semen quality parameters of breeding bulls during summer season (June-August). Adult Frieswal bulls (10) were randomly distributed into two groups i.e. in traditional (TG) and modified (MG) design sheds. The sides of individual pens in TG (east-west oriented) and MG (north-south oriented) were covered and open, respectively with equal floor space/bull in both sheds. Respiration rate (RR), heart rate (HR), rectal temperature (RT), body coat and scrotal temperature were recorded in the morning (8.00 to 9.00 AM), and before and after shower in the afternoon (2.00 to 4.00 PM) at weekly interval. Biweekly semen ejaculates were evaluated for volume, concentration and initial motility. Average THI did not vary over the periods and was higher in the afternoon than in the morning in both types of the sheds. Average RT and RR in bulls of both sheds increased significantly in the afternoon than in the morning. HR increased during afternoon period in TG; however, it did not differ significantly in MG. Average RR, body coat and scrotal temperature were higher even after shower than in morning in TG, however, no difference was observed for these parameters in MG. Improvement in initial progressive motility was recorded in bulls of modified sheds after fourth fortnight. The present study revealed better physiological responses and semen quality attributes in bulls kept in modified sheds with open sides of individual pens.